The Anti-Inflammatory Effects of Shinbaro3 Is Mediated by Downregulation of the TLR4 Signalling Pathway in LPS-Stimulated RAW 264.7 Macrophages - Hwa-Jin Chung; Wonil Koh; Won Kyung Kim; Joon-Shik Shin; Jinho Lee; Sang Kook Lee; In-Hyuk Ha (Mediators of Inflammation)
Shinbaro3, a formulation derived from the hydrolysed roots of Harpagophytum procumbens var. sublobatum (Engl.) Stapf, has been clinically used in the pharamacopuncture treatment of arthritis in Korea. In the present study, Shinbaro3 inhibited NO generation in LPS-induced RAW 264.7 cells in a dose-dependent manner. Shinbaro3 also downregulated the mRNA and protein expression of inflammatory mediators in a dose-dependent manner. Three mechanisms explaining the effects of Shinbaro3 in RAW 264.7 cells were identified as follows: (1) inhibition of the extracellular signal-regulated kinase 1 and 2 (ERK1/2), stress-activated protein kinase (SAPK)/c-Jun N-terminal protein kinase (JNK), and p38 mitogen-activated protein kinase (MAPK) pathways; (2) suppression of IκB kinase-α/β (IKK-α/β) phosphorylation and nuclear factor-kappa B (NF-κB) subunits in the NF-κB pathway, which are involved in MyD88-dependent signalling; and (3) downregulation of IFN-β mRNA expression via inhibition of interferon regulatory factor 3 (IRF3) and Janus-activated kinase 1 (JAK1)/signal transducer and activator of transcription 1 (STAT1) phosphorylation, which is involved in TRIF-dependent signalling. Shinbaro3 exerted anti-inflammatory effects in LPS-stimulated RAW 264.7 macrophage cells through modulation of the TLR4/MyD88 pathways, suggesting that Shinbaro3 is a novel anti-inflammatory therapeutic candidate in the field of pharmacopuncture.